Transition metal doped defect-rich molybdenum disulfide / biomass carbon composite aerogel as well as preparation method and application thereof
By doping transition metals into the biomass carbon aerogel domain boundary framework and introducing defect-rich molybdenum disulfide, the problem of easy agglomeration and single defect type is solved, and its adsorption ability to cesium ions and strontium ions is significantly improved.
Patent Information
- Application Number
- CN202510442273.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-09
- Publication Date
- 2025-06-13
AI Technical Summary
Existing molybdenum disulfide nanosheets are prone to agglomeration, reducing their adsorption capacity, and the defect type is mainly sulfur vacant, which is not conducive to the efficient adsorption of cesium ions and strontium ions.
By doping transition metals into the biomass carbon aerogel domain boundary framework, defect-rich molybdenum disulfide is introduced, its base surface is activated, more sulfur atoms with metal binding capacity are exposed, and adsorption active sites are increased.
The adsorption capacity of the composite aerogel to cesium and strontium ions is significantly improved, and efficient selective adsorption of radionuclides is achieved.
Smart Images

Figure CN120132787A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aerogels, and particularly relates to a transition metal-doped defective molybdenum disulfide / biomass carbon composite aerogel, a preparation method thereof, and an application thereof. Background Art
[0002] With the increasingly depletion of fossil fuel resources and the serious environmental pollution caused by their large-scale use, safe, economical, and clean nuclear energy has been favored by the whole world. As an important part of the energy structure and low-carbon power supply, the scale and quantity of nuclear power plants are steadily increasing. However, the occurrence of nuclear accidents often generates a large amount of radioactive waste liquid, and its large-scale discharge will cause serious long-term damage to the environment and pose a serious risk to human health. Among them, cesium-137 and strontium-90 are considered to be the main sources of radioactivity and the substances with the highest safety risks in nuclear waste due to their long half-lives. Therefore, it is crucial to efficiently and selectively remove cesium ions and strontium ions from nuclear wastewater with complex compositions and properties for the global environment and human health.
[0003] The adsorption method has become an effective method for removing radioactive nuclides such as cesium ions and strontium ions due to its advantages such as low cost and convenient operation. Molybdenum disulfide is a transition metal sulfide with a two-dimensional layered structure, and the soft base ion S in its structure 2- has strong affinity and selectivity for soft acid ions such as cesium ions and strontium ions, and has become a promising class of radioactive nuclide adsorbents. However, due to the van der Waals force between layers and high surface energy, molybdenum disulfide nanosheets are prone to agglomeration, reducing the exposure of active sites and affecting its adsorption capacity. Using biomass carbon aerogel as the confinement framework of molybdenum disulfide can effectively solve its agglomeration problem. In addition, molybdenum disulfide has fewer intrinsic adsorption active sites, and more defects or other active sites need to be introduced. Heteroatom doping is an effective modification method to improve the activity of molybdenum disulfide. The doping of heteroatoms in the lattice structure can change the electronic structure of the material surface, and at the same time, the lattice defects generated by doping can further expose more adsorption active sites and improve its adsorption performance. Engineering design of molybdenum disulfide defects is an effective method to achieve its high-efficiency adsorption performance of cesium ions and strontium ions. However, most of the reported defect types are sulfur vacancies at present, and in molybdenum disulfide used for removing cesium ions and strontium ions in water, sulfur atoms are the main active sites for binding with cesium ions and strontium ions, and the large loss of sulfur atoms is obviously not conducive to the improvement of its adsorption performance. Therefore, reasonable and controllable regulation of defect types is still challenging. Summary of the Invention
[0004] Aiming at the above-mentioned deficiencies, the purpose of the present invention is to provide a transition metal-doped defective molybdenum disulfide / biomass carbon composite aerogel, a preparation method thereof and an application thereof. The prepared composite aerogel exposes more sulfur atoms with metal-binding ability, greatly increasing the number of adsorption active sites, thereby promoting its adsorption ability for radionuclides.
[0005] The technical solution adopted is as follows:
[0006] In the first aspect, a preparation method of a transition metal-doped defective molybdenum disulfide / biomass carbon composite aerogel of the present invention includes the following steps:
[0007] (1) Preparation of biomass carbon aerogel: Chitosan is dispersed in an acetic acid solution, stirred and dissolved to obtain a chitosan dispersion, and then a glutaraldehyde cross-linking agent is added for cross-linking reaction to obtain a chitosan-based hydrogel, which is freeze-dried to obtain a chitosan aerogel; then the chitosan aerogel is placed in a tube furnace and pyrolyzed at 400-800 °C under an inert gas atmosphere to obtain a biomass carbon aerogel;
[0008] (2) Preparation of transition metal-doped defective molybdenum disulfide / biomass carbon composite aerogel: A molybdenum source, a sulfur source, a transition metal source and water are mixed evenly to obtain a mixed solution. The biomass carbon aerogel prepared in step (1) is soaked in the above mixed solution, and then sodium citrate is added, and it is placed in a reaction kettle for hydrothermal reaction at 160-220 °C to obtain a transition metal-doped defective molybdenum disulfide / biomass carbon composite aerogel.
[0009] Further, the transition metal source in step (2) is one or more of their soluble salts of vanadium, manganese, cobalt, iron, nickel, zirconium and tungsten.
[0010] Further, the molybdenum source in step (2) is one or several of ammonium molybdate, sodium molybdate, molybdenum chloride, ammonium tetrathiomolybdate, and the sulfur source is one or several of thioacetamide, thiourea, and cysteine.
[0011] Further, the concentration of the sulfur source is 30-150 mmol / L, and the molar ratio of the molybdenum source to the sulfur source is 1:(2-10) in terms of Mo:S; the molar ratio of the transition metal to the molybdenum source is (0.01-2):1 in terms of transition metal:Mo.
[0012] Further, the mass ratio of the biomass carbon aerogel to the sum of the masses of the molybdenum source, the sulfur source, and the transition metal source is 1:(20-100).
[0013] Further, the mass ratio of the biomass carbon aerogel to sodium citrate in step (2) is 1:(0.5-1.5).
[0014] Further, in step (1), the chitosan aerogel is placed in a tubular furnace and pyrolyzed at 400 - 800 °C under an N 2 atmosphere at a heating rate of 5 °C·min -1 for 2 - 8 h.
[0015] Second, a transition metal - doped defective molybdenum disulfide / biomass carbon composite aerogel of the present invention is prepared by the preparation method described in the above solution.
[0016] Third, an adsorbent includes the transition metal - doped defective molybdenum disulfide / biomass carbon composite aerogel described in the above solution.
[0017] Fourth, application of the transition metal - doped defective molybdenum disulfide / biomass carbon composite aerogel described in the above solution in the treatment of radioactive wastewater containing cesium ions and strontium ions.
[0018] In the above - mentioned technical solution,
[0019] First, using chitosan as a matrix, a chitosan hydrogel precursor is obtained by glutaraldehyde cross - linking. A porous biomass carbon aerogel with self - floating performance is obtained through freeze - drying and pyrolysis under inert gas protection. Then the biomass carbon aerogel is immersed in a mixed solution of a sulfur source, a molybdenum source, and a transition metal source. Transition metal - doped molybdenum disulfide is in - situ grown in the biomass carbon aerogel by a hydrothermal method, and sodium citrate is added to induce the vertical growth of transition metal - doped molybdenum disulfide in the biomass carbon aerogel. The doping of transition metals will be accompanied by the introduction of vacancies, activating the inert basal plane of molybdenum disulfide, and a reasonable defect design can be further achieved by adjusting the type and content of transition metals and the concentration of the sulfur source, so that more sulfur atoms with metal - binding ability are exposed, greatly increasing the number of adsorption active sites, thereby promoting its adsorption ability for radionuclides.
[0020] The present invention obtains defective molybdenum disulfide by a transition metal doping strategy, and then controllably assembles it with a biomass carbon aerogel to construct a material for highly efficient and selective adsorption of cesium ions and strontium ions. This composite aerogel can be directly used as an adsorbent. More sulfur atoms with metal - binding ability are exposed in this composite aerogel, greatly increasing the number of adsorption active sites and promoting its adsorption ability for radionuclides.
[0021] Thus, the beneficial effects of the present invention are as follows:
[0022] 1. The present invention uses biomass carbon aerogel as the confinement framework for the growth of molybdenum disulfide, which can not only effectively solve the problem of easy aggregation of molybdenum disulfide, but also the unique three-dimensional network porous structure of biomass carbon aerogel is conducive to the rapid entry of cesium ions and strontium ions into the internal structure of the composite adsorbent, and realizes the selective adsorption of cesium ions and strontium ions through the active sites on the molybdenum disulfide grown on the biomass carbon aerogel.
[0023] 2. The present invention obtains defect-rich molybdenum disulfide by transition metal doping, exposes more sulfur atoms with metal-binding ability, greatly increases the number of adsorption active sites, and promotes its adsorption ability for radionuclides. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 XRD pattern of the transition metal-doped defect-rich molybdenum disulfide / biomass carbon composite aerogel prepared in Example 1 of the present invention;
[0025] Figure 2 Scanning electron microscopy image of the transition metal-doped defect-rich molybdenum disulfide / biomass carbon composite aerogel prepared in Example 1 of the present invention;
[0026] Figure 3 Transmission electron microscopy image of the transition metal-doped defect-rich molybdenum disulfide / biomass carbon composite aerogel prepared in Example 1 of the present invention;
[0027] Figure 4 Adsorption efficiency graph of cesium ions and strontium ions by the transition metal-doped defect-rich molybdenum disulfide / biomass carbon composite aerogel prepared in Example 1 of the present invention.
[0028] Figure 5 EPR graph of the transition metal-doped defect-rich molybdenum disulfide / biomass carbon composite aerogel prepared in Example 1 of the present invention.
[0029] Figure 6 Adsorption efficiency graph of cesium ions and strontium ions by the transition metal-doped defect-rich molybdenum disulfide / biomass carbon composite aerogel prepared in Example 1 of the present invention. DETAILED DESCRIPTION OF THE INVENTION
[0030] The present invention will be described in detail below through specific examples, but the uses and purposes of these exemplary embodiments are only used to illustrate the present invention, and do not constitute any form of limitation to the actual protection scope of the present invention, nor will the protection scope of the present invention be limited thereto.
[0031] Example 1
[0032] A preparation method of a transition metal-doped defect-rich molybdenum disulfide / biomass carbon composite aerogel in this example includes the following steps:
[0033] (1) Preparation of biomass carbon aerogel: 0.5 g of chitosan was dispersed in 50 mL of 0.5 mol / L acetic acid solution and stirred at 80 °C to dissolve to obtain a chitosan dispersion. Subsequently, 1 mL of 5 wt% glutaraldehyde cross-linking agent was added for cross-linking reaction to obtain a chitosan-based hydrogel, and the chitosan aerogel was obtained by freeze-drying. Then, the chitosan aerogel was placed in a tube furnace and pyrolyzed at 800 °C under N 2 atmosphere at a heating rate of 5 °C·min -1 for 8 h to obtain the biomass carbon aerogel;
[0034] (2) Preparation of transition metal-doped defective molybdenum disulfide / biomass carbon composite aerogel: 0.494 g of ammonium molybdate, 0.14 g of sodium vanadate, 0.092 g of ammonium tungstate and 1.599 g of thiourea were weighed and added to 20 mL of deionized water, stirred evenly to obtain a mixed solution. 0.03 g of the biomass carbon aerogel prepared in step (1) was immersed in the above mixed solution for 12 h, then 0.021 g of sodium citrate was added, and it was placed in a reaction kettle for hydrothermal reaction at 220 °C for 24 h to obtain the transition metal-doped defective molybdenum disulfide / biomass carbon composite aerogel.
[0035] Example 2
[0036] A preparation method of a transition metal-doped defective molybdenum disulfide / biomass carbon composite aerogel in this example includes the following steps:
[0037] (1) Preparation of biomass carbon aerogel: 0.5 g of chitosan was dispersed in 50 mL of 0.5 mol / L acetic acid solution and stirred at 80 °C to dissolve to obtain a chitosan dispersion. Subsequently, 0.8 mL of 5 wt% glutaraldehyde cross-linking agent was added for cross-linking reaction to obtain a chitosan-based hydrogel, and the chitosan aerogel was obtained by freeze-drying. Then, the chitosan aerogel was placed in a tube furnace and pyrolyzed at 600 °C under N 2 atmosphere at a heating rate of 5 °C·min -1 for 8 h to obtain the biomass carbon aerogel;
[0038] (2) Preparation of transition metal-doped defective molybdenum disulfide / biomass carbon composite aerogel: 0.494 g of ammonium molybdate, 0.28 g of sodium vanadate, 0.092 g of ammonium tungstate and 1.599 g of thiourea were weighed and added to 20 mL of deionized water, stirred evenly to obtain a mixed solution. 0.03 g of the biomass carbon aerogel prepared in step (1) was immersed in the above mixed solution for 12 h, then 0.021 g of sodium citrate was added, and it was placed in a reaction kettle for hydrothermal reaction at 220 °C for 12 h to obtain the transition metal-doped defective molybdenum disulfide / biomass carbon composite aerogel.
[0039] Example 3
[0040] A preparation method of a transition metal-doped defective molybdenum disulfide / biomass carbon composite aerogel according to this embodiment includes the following steps:
[0041] (1) Preparation of biomass carbon aerogel: Dissolve 0.5 g of chitosan in 50 mL of 0.5 mol / L acetic acid solution, stir and dissolve at 80 °C to obtain a chitosan dispersion, then add 1 mL of 5 wt% glutaraldehyde cross-linking agent for cross-linking reaction to obtain a chitosan-based hydrogel, and obtain a chitosan aerogel by freeze-drying. Then place the chitosan aerogel in a tube furnace and pyrolyze it at 800 °C under N 2 atmosphere at a heating rate of 5 °C·min -1 for 4 h to obtain a biomass carbon aerogel;
[0042] (2) Preparation of transition metal-doped defective molybdenum disulfide / biomass carbon composite aerogel: Weigh 0.494 g of ammonium molybdate, 0.183 g of ammonium tungstate and 1.599 g of thiourea respectively, add them to 30 mL of deionized water and stir evenly to obtain a mixed solution. Immerse 0.03 g of the biomass carbon aerogel prepared in step (1) in the above mixed solution for 12 h, then add 0.021 g of sodium citrate, place it in a reaction kettle and carry out hydrothermal reaction at 180 °C for 24 h to obtain a transition metal-doped defective molybdenum disulfide / biomass carbon composite aerogel.
[0043] Example 4
[0044] A preparation method of a transition metal-doped defective molybdenum disulfide / biomass carbon composite aerogel according to this embodiment includes the following steps:
[0045] (1) Preparation of biomass carbon aerogel: Dissolve 0.5 g of chitosan in 50 mL of 0.5 mol / L acetic acid solution, stir and dissolve at 80 °C to obtain a chitosan dispersion, then add 1 mL of 5 wt% glutaraldehyde cross-linking agent for cross-linking reaction to obtain a chitosan-based hydrogel, and obtain a chitosan aerogel by freeze-drying. Then place the chitosan aerogel in a tube furnace and pyrolyze it at 400 °C under N 2 atmosphere at a heating rate of 5 °C·min -1 for 6 h to obtain a biomass carbon aerogel;
[0046] (2) Preparation of transition metal-doped defective molybdenum disulfide / biomass carbon composite aerogel: Weigh 0.494 g of ammonium molybdate, 0.28 g of sodium vanadate, 0.092 g of ammonium tungstate, and 1.599 g of thiourea respectively, add them to 50 mL of deionized water, stir evenly to obtain a mixed solution, soak 0.03 g of the biomass carbon aerogel prepared in step (1) in the above mixed solution for 12 h, then add 0.021 g of sodium citrate, place it in a reaction kettle, and carry out hydrothermal reaction at 160 °C for 48 h to obtain the transition metal-doped defective molybdenum disulfide / biomass carbon composite aerogel.
[0047] Experimental tests:
[0048] Figure 1 This is the XRD pattern of the transition metal-doped defective molybdenum disulfide / biomass carbon composite aerogel prepared in Example 1 of the present invention. As Figure 1 can be seen, the characteristic diffraction peaks of (002), (100), and (110) of molybdenum disulfide appear in the composite aerogel, indicating that molybdenum disulfide has grown successfully in the biomass carbon aerogel.
[0049] Figure 2 This is the scanning electron microscope image of the transition metal-doped defective molybdenum disulfide / biomass carbon composite aerogel prepared in Example 1 of the present invention. It can be seen from the figure that the composite aerogel shows a continuous and uniform porous structure, and the flaky molybdenum disulfide grows vertically and evenly on the surface of the composite aerogel.
[0050] Figure 3 This is the transmission electron microscope image of the transition metal-doped defective molybdenum disulfide / biomass carbon composite aerogel prepared in Example 1 of the present invention. It can be seen from the figure that the size of the grown molybdenum disulfide is about 500 nm.
[0051] Figure 4 This is the elemental mapping image of the transition metal-doped defective molybdenum disulfide / biomass carbon composite aerogel prepared in Example 1 of the present invention. The elements Mo, S, V, W from the doped molybdenum disulfide and the element C belonging to the biomass carbon aerogel are detected in the figure, and each element is evenly dispersed, indicating that V and W have been successfully doped into molybdenum disulfide and are evenly dispersed in the biomass carbon aerogel.
[0052] Figure 5 This is the EPR pattern of the transition metal-doped defective molybdenum disulfide / biomass carbon composite aerogel prepared in Example 1 of the present invention. It can be seen from the figure that a peak of vacancies is observed at g = 2.003, indicating that the doping of V and W has successfully introduced defects into molybdenum disulfide.
[0053] Figure 6This is the adsorption efficiency diagram of the transition metal-doped defective molybdenum disulfide / biomass carbon composite aerogel prepared in Example 1 of the present invention for cesium ions and strontium ions. As can be seen from the figure, the adsorption capacities of the molybdenum disulfide-MXene / biomass carbon composite aerogel for cesium ions and strontium ions are 139.8 mg / g and 90.9 mg / g respectively, and the adsorption equilibrium for cesium ions and strontium ions is reached at 4 h.
[0054] The series of detailed descriptions listed above are only specific descriptions of the feasible embodiments of the present invention, and they are not intended to limit the protection scope of the present invention. Any equivalent embodiments or changes made without departing from the technical spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a transition metal-doped defect-rich molybdenum disulfide / biomass carbon composite aerogel, characterized in that: The following steps are involved: (1) Preparation of biomass carbon aerogel: chitosan is dispersed in an acetic acid solution, stirred and dissolved to obtain a chitosan dispersion, and then a glutaraldehyde crosslinking agent is added to carry out a crosslinking reaction to obtain a chitosan-based hydrogel, and chitosan aerogel is obtained by freeze drying; the chitosan aerogel is then placed in a tubular furnace at 400-800°C and pyrolyzed under an inert gas atmosphere to obtain a biomass carbon aerogel; (2) Preparation of transition metal-doped defect-rich molybdenum disulfide / biomass carbon composite aerogel: a molybdenum source, a sulfur source, a transition metal source and water are uniformly mixed to obtain a mixed solution, the biomass carbon aerogel prepared in step (1) is immersed in the above mixed solution, and then sodium citrate is added, and the mixture is placed in a reactor for hydrothermal reaction at 160-220° C. to obtain a transition metal-doped defect-rich molybdenum disulfide / biomass carbon composite aerogel.
2. The method for preparing the transition metal-doped defect-rich molybdenum disulfide / biomass carbon composite aerogel according to claim 1, characterized in that: The transition metal source in step (2) is one or more soluble salts of vanadium, manganese, cobalt, iron, nickel, zirconium and tungsten.
3. The method for preparing the transition metal-doped defect-rich molybdenum disulfide / biomass carbon composite aerogel according to claim 1, characterized in that: In step (2), the molybdenum source is one or more of ammonium molybdate, sodium molybdate, molybdenum chloride, and ammonium tetrathiomolybdate, and the sulfur source is one or more of thioacetamide, thiourea, and cysteine.
4. The method for preparing the transition metal-doped defect-rich molybdenum disulfide / biomass carbon composite aerogel according to claim 1, characterized in that: The concentration of the sulfur source is 30-150 mmol / L, the molar ratio of the molybdenum source to the sulfur source is 1:(2-10) when measured as Mo:S; and the molar ratio of the transition metal to the molybdenum source is (0.01-2):1 when measured as transition metal:Mo.
5. The method for preparing the transition metal-doped defect-rich molybdenum disulfide / biomass carbon composite aerogel according to claim 1, characterized in that: The ratio of the mass of the biomass carbon aerogel to the sum of the mass of the molybdenum source, the sulfur source and the transition metal source is 1:(20-100).
6. The method for preparing the transition metal-doped defect-rich molybdenum disulfide / biomass carbon composite aerogel according to claim 1, characterized in that: The mass ratio of the biomass carbon aerogel to sodium citrate in step (2) is 1:(0.5-1.5).
7. The method for preparing the transition metal-doped defect-rich molybdenum disulfide / biomass carbon composite aerogel according to claim 1, characterized in that: In step (1), the chitosan aerogel is placed in a tubular furnace at 400-800°C and N2 atmosphere at 5°C·min -1 The heating rate is pyrolysis for 2-8h.
8. A transition metal-doped defect-rich molybdenum disulfide / biomass carbon composite aerogel, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.
9. An adsorbent, characterized in that It comprises the transition metal-doped defect-rich molybdenum disulfide / biomass carbon composite aerogel as described in claim 8.
10. Use of the transition metal-doped defect-rich molybdenum disulfide / biomass carbon composite aerogel according to claim 8 in the treatment of radioactive wastewater containing cesium ions and strontium ions.